Dinamika Literasi Masyarakat Salatiga: Perbandingan Indeks Pembangunan Literasi dan Indeks Literasi 2022 - Budi Warsito; Harjum Muharam; Arief Rachman Hakim; Endang Fatmawati; Heriyanto; Yanuar Yoga Prasetyawan (Perpustakaan Nasional, 2023)
The examination of the Community Literacy Development Index (IPLM) juxtaposed with the Community Literacy Index (ILM) was undertaken as a foundational reference for the establishment of developmental policies and performance metrics. This research was driven by dual objectives: firstly, to ascertain the magnitude of the IPLM within the confines of Salatiga City, and secondly, to gauge the ILM within the same region. The analysis concerning the IPLM was executed to assess the state of libraries across Salatiga, encompassing facets such as spatial distribution of libraries, their respective collections, the competencies of library staff, and their patron demographics. The ILM investigation specifically narrowed its focus to the sub-district echelon, eliciting responses from 400 participants aged between 15 and 64 years. Emerging from the IPLM investigation, it was discerned that out of the 164 libraries included in the census, the composition was as follows: 20 public libraries, 129 school-affiliated libraries, 4 university libraries, and a further 10 specialized libraries. To further categorize by district, Argomulyo accounted for 32 libraries, Tingkir had 37, Sidomukti held 41, and Sidorejo hosted 53. Cumulatively, Salatiga City’s IPLM was determined to be 72.83, placing it within the moderate range (aligning with standard benchmarks). In parallel, the ILM analysis unveiled an overall score of 63.14 for Salatiga City, classifying it within the median spectrum. Within this, Argomulyo District took the lead with an ILM score of 66.30, while Tingkir District lagged with a score of 54.66.